The role of rye bran and antibiotics on the digestion, fermentation process and short-chain fatty acid production and absorption in an intact pig model. Issue 7 (19th March 2021) - Xu, Yetong; Bolvig, Anne Katrine; McCarthy-Sinclair, Brendan; Marco, Maria L.; Bach Knudsen, Knud Erik; Hedemann, Mette Skou; Lærke, Helle Nygaard
Abstract : Rye bran diet induced different DF degradation processes and SCFA profile compared with refined wheat cellulose, while antibiotics had marginal effects on digestibility and DF degradation but hampered butyrate production. Abstract : The effects of arabinoxylan (AX)-rich rye bran based diet (RB) and antibiotics on digestion, fermentation and short-chain fatty acids (SCFA) absorption were studied compared with an iso-dietary fibre (DF) cellulose based diet (CEL). Thirty female pigs (body weight 72.5 ± 3.9 kg) were fed a standard swine diet in week 1, CEL as wash-out for bran-associated bioactive components in week 2 and then divided into 3 groups fed either the CEL ( n = 10) or RB ( n = 20) for 2 weeks, where 10 pigs from RB had daily intramuscular antibiotic injections (RB+) and the other 10 pigs were untreated (RB−) in week 4. In RB, the degradation of AX mainly occurred in caecum and proximal colon ( P < 0.01) and to a higher extent than cellulose, which on the other hand, irrespective of antibiotic treatment, was less degraded in the RB groups than in the CEL ( P < 0.01). The apparent digestibility of fat and protein in the distal small intestine was lower for RB than CEL ( P < 0.05), the protein digestibility remained lower in most of the colon, and the digestibility was not affected by treatment with antibiotics. The colonic concentrations of SCFA, acetate and propionate as well as the butyrate concentration in the distal colon were lower with the RB treatments compared with CEL ( P < 0.01). Caecal butyrate concentrations were on the other hand higher, and a significant reduction was seen with antibiotic treatment ( P < 0.001). The daily net absorption of SCFA and acetate was lower with RB than with CEL ( P < 0.01). In conclusion, RB resulted in different DF degradation processes and SCFA production compared with CEL, whereas antibiotic treatment had marginal effects on the intestinal DF degradation but hampered butyrate production.